An international comparative study of fitness and skill in elite U16 basketball players - Peters, D. M.; Donovan, M.; Bacliunas, M.; Stonkus, S. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Fitness and skill are considered key components of basketball game play and eventual team success, with tests related to key performance indicators (KPI) validated through their ability to discriminate between levels of performance. Purpose: To compare group performance on sport specific fitness tests and KPI-related skill tests in elite male youth basketball players from one high ranked and one low ranked basketball nation. Method: Thirty three male U16-year-old elite and/or national representative players from a high ranked basketball nation (in top five of Division A at the 2005 World Championships, n=16) and a low ranked basketball nation (between 6-10th place in Division B at the 2005 World Championships, n=17) completed four sport specific fitness tests: 20 metre sprint (Sprint); countermovement standing vertical jump (CMJ); standing vertical jump from 90 degree squat (SVJ); Abalakov jump (AJ); and three KPIrelated skill tests: ball dribbling (BD); jump shot (JS); and free throws (FT) using protocols adapted from Balciunas et al., (2006). The best score or time from three attempts was used for group comparison using paired samples t-tests (p<.05). Results: There were no significant group differences found between the Division A and Division B teams for height (1.92±.07m vs 1.86±.09m, p=.07), weight (72.6±5.4kg; Div B 74.2±9.1kg, p=.55), 20m sprint time (3.13±.20secs vs 3.15±.09secs, p=.66), CMJ (40.4±3.1cm vs 40.5±4.8cm, p=.93), SVJ (38.5±3.3cm vs 38.9±4.7cm, p=.79) and BD (7.79±.49secs vs 7.82±.51secs). Significant group differences between the Division A and Division B nations were apparent for BMI (19.8±1.2 kg.m2 vs 21.3±1.3kg.m2, t=3.32, p<.01, eta2=.26), AJ (50.4±3.7cms vs 45.1±5.0cms, t=3.42, p<.01, eta2=.27), JS (12.2±2.7 vs 8.5±3.6, t=3.31, p<.01, eta2=.26) and FT (22.8±3.4 vs 18.8±6.6, t=2.25, p<.05, eta2=.14). Conclusions: As a group, and being similar in positional representation, the higher ranked nation demonstrated a lower weight to height ratio, suggesting a taller and leaner player profile, although more accurate body composition measurement is recommended in future studies. The higher-ranking nation were also found to perform better at arguably the most game specific vertical jump (the Abalakov jump) and the two most `score-outcome related` skill tests. Relative body composition and these three tests may therefore be the most useful for discrimination between levels of performance in elite male youth basketball. Without suggestion of causality, specific physical training and technique/skill practice are recommended for less successful basketball teams in order to improve these seemingly performance related fitness and skill attributes.